Criminological Analysis in Drug Abuse Cases (Study at Rumah Damai Foundation Semarang) (Law Research Review Quarterly, 2020)
Narcotics, psychotropic substances and other addictive substances commonly called narcotics are among the things that are often misused in human life. Drugs have negative impacts both physically, psychologically, economically. Drugs are a group of substances that generally have a risk of addiction for the wearer. At first, drugs were only used in the world of health as psychotropic drugs used to anesthetize patients who were going to have surgery or other treatments. But along with the times, the use of drugs is widely abused for negative things resulting from use outside the limits or over dosage. The effects of narcotics alone can be dangerous for the user and the people around him. Most drug users are teenagers. One of the main factors that influence adolescents abusing drugs is a factor from families who pay less attention to their children in addition to environmental factors that are also very influential. The biggest concern from the impact of using narcotics consumed continuously will eventually lead to lost generation. In accordance with Law no. 35 of 2009 drug users or addicts are not categorized as criminals who deserve to be jailed, but as victims who deserve to be healed by means of rehabilitation or other treatment with the intention of recovery for something more productive.